Blood microparticles are a component of immune modulation in red blood cell transfusion. Issue 8 (2nd June 2020) - Pinheiro, Marion Klea; Tamagne, Marie; Elayeb, Rahma; Andrieu, Muriel; Pirenne, France; Vingert, Benoît
Abstract : Patients may display alloimmunization following transfusion. Microparticles (MPs) released into the blood are present in transfusion products. We show that MPs can modulate the immune system, CD4 + T‐cell, and humoral responses, through their concentration, cellular origin and phenotype, and should therefore be considered to reduce the immune impact of transfusion.